Linking plant demography, ecological dynamics and population genetics across space and time - NAHAA ALOTAIBI (2021)
Seagrasses structure some of the world's key coastal ecosystems presently in decline due to human activities and global change. Population genetic analysis is an important tool for understanding genetic resources and adaptation, with great potential to inform marine spatial planning and other management decisions. This thesis addresses questions regarding the genetic diversity of extant populations, and how this information can aid current conservation and restoration efforts. In chapter 2, I aimed to assess the use of an existing panel of 15 microsatellites as a tool for understanding population genetic structure in widely distributed seagrass species, Zostera marina, from five meadows around the UK. These results from the pilot study showed that the proposed panel of microsatellites can provide high quality data from seagrass samples. Importantly, all microsatellite loci were polymorphic at this scale. In chapter 3, I estimated allelic diversity in eelgrass, Z. marina, at five sites around the Isles of Scilly Special Area of Conservation, UK, in 2010 and compared this to 23 years of annual ecological monitoring data (1996-2018). I found low genetic diversity and long-term declines in abundance amongst five sites around the Isles of Scilly, which is an isolated location approximately 25 miles off the southwest tip of the UK. In chapter 4, I further developed Z. marina around the Isles of Scilly as a natural model system to compare measures of resilience derived from demographic and morphological trait variability, long-term population dynamics and population genetics, which, is rarely done in a single study. I found allele richness, spatial variability in shoot morphology, resilience in local shoot dynamics were correlated and separately that resistance at a broader vegetation spatial scale are correlated. In chapter 5, I aimed to quantify genetic variation in eelgrass, Z. marina, and identify patterns associated with local environment from 18 meadows across the southwest of England and West of Wales, clustered into six sites: Gelliswick (1 seagrass meadow), Looe (1 seagrass meadow), Plymouth (6 seagrass meadows), Salcombe (1 seagrass meadow), Torbay (6 seagrass meadows), Weymouth (3 seagrass meadows). Across the southwest of England and West of Wales, eelgrass was not in Hardy-Weinberg equilibrium, indicating some local restriction of gene flow within sites. I also explored spatial structure through quantifying isolation by distance and inferred that connectivity between local sites on the coast potentially mitigates against population genetic restriction at the broader spatial scale, I estimated genetic variation in eelgrass between meadows and compared this to six environmental variables – depth, photosynthetically available light at the seabed (PAR), the coefficient of light attenuation (KDPAR), kinetic energy due to waves (KeW) and kinetic energy due to currents (KeC). I found that intermediate depths were associated with the highest allele richness and clonal richness, with intermediate available light associated with minimum clonal richness. Overall, my study highlights the need to understand the link between population genetics and environmental variables to improve responses to threats against this internationally important ecosystem.